Social Justice and the Search for the Common Good in Southern Africa: A Theological Perspective - Kasera, Basilius (Stellenbosch Theological Journal, 2023)
Social injustice and inequality create existential worries and social instability. Public theology, as a method rather than as a discipline, developed as a response to fortify Christian witness in the public arena and to answer to issues such as social injustice. This article builds on this theological method for social engagement and on the inherent social capital that religion holds to produce the common good in a secular environment. As part of reflecting upon the significance of theology in the public sphere, I first will examine the role theology can play to shape our social vision. Secondly, I will examine how the notions of covenant and neighbourliness could be providing a turning point regarding social justice. Thirdly, I address the search for the common good as God's tool to inform alternative and humane associational life. Fourthly, the article will explore theology's role to inform and create a vibrant civic society. The dialogue partners in the article are intentionally chosen to formulate a theological pedagogy distinctive from defensive, and at times violent, postures witnessed in social justice dialogues. I aim to create a space for a more objective examination of habits and practices in search of a fuller description and embodiment of God's Kingdom in Southern Africa. The article explores the following question, how can theology, through pursuing the common good, become a significant social capital generator to influence social justice in Southern Africa?